Rh(iii) hydroxocomplexes speciation using HPLC-ESI-MS. Issue 20 (13th May 2020) - Volchek, Victoria V.; Berdyugin, Semen N.; Shuvaeva, Olga V.; Sheven, Dmitriy G.; Vasilchenko, Danila B.; Korenev, Sergey V.
Abstract : The comprehensive identification of polynuclear species of Rh(iii ) was successfully executed by HPLC-ESI-MS combination. Abstract : A mixture of rhodium(iii ) hydroxocomplexes formed during the polycondensation process in alkaline media has been fully characterized by the hyphenated high performance liquid chromatography with electrospray ionization mass spectrometry (HPLC-ESI-MS). The baseline separation was achieved using reverse phase ion-pair chromatography (RP-IP-HPLC) in gradient elution mode. When using SDS as the ion pair, the formation of all types of its associates with the molecules of acetonitrile, as well as oligomers of rhodium aquahydroxocomplexes, etc. was taken into consideration. As a result, it was shown that the test mixture is presented by [Rh(H2 O)6 ] 3+, [Rh2 (μ-OH)2 (H2 O)8 ] 4+, [Rh3 (μ-OH)4 (H2 O)10 ] 5+, [Rh4 (μ-OH)6 (H2 O)12 ] 6+ .